CONCEPTUALIZING ISLAMIC BASED EDUCATION: An attempt toward Islamization of Educational System in Aceh - Hasan Basri (Jurnal Ilmiah Didaktika, 2015)
This study proves that Islam has a unique concept of education and constructive values that can be applied in educational system. Discussion on Islamic education has not ended yet; that is why to reveal the Islamic educational values deriving from the primary sources of Islam, the Qur’an and Sunna (prophetic tradition), is not insignificant in the context of educational system in Aceh. Since Aceh has specific privilege in the fields of education, religion, and culture, it is crucial to break up earth the Islamic values and apply them into education programs. Realizing such programs should take accurate and strategic steps through islamization of education, integration of values, and internationalization of way of thinking. Besides, curriculum, method, system, policy, and dichotomy of educational system must be reformed concurrently.